DNA barcodes, expanded distribution, and redescription of Apanteles hemara Nixon, 1965 (Hymenoptera, Braconidae, Microgastrinae), a potential biocontrol species against amaranth leaf-webbers in Africa - Jose Fernandez-Triana; Melanie Beaudin; Kees van Achterberg; Mawufe K. Agbodzavu; Stephen T.O. Othim; Faith W. Nyamu; Komi K.M. Fiaboe (Journal of Hymenoptera Research, 2017)
The microgastrine parasitoid wasp Apanteles hemara Nixon, 1965, is currently being considered as a potential biocontrol agent of amaranth leaf-webber pests in Africa. To facilitate future research and identification of the species, we characterize it from an integrative taxonomy perspective by providing a comprehensive morphological redescription, extensive illustrations (including the first images of the holotype), DNA barcodes, wasp biology, host data (Choreutidae and Crambidae caterpillars), and updated geographical distribution of the species (including eight new country records). Despite a wide distribution across four major biogeographical regions (mostly within the Old World tropics), the species seems to be relatively uniform from a molecular and morphological perspective, based on studied specimens from Africa and Asia.